Multicomponent diffusion in solute-containing micelle and microemulsion solutions - Musnicki, Wyatt J (Langmuir : the ACS journal of surfaces and colloids, 2014)
Holographic interferometry was used to obtain new results for the four coefficients that determine rates of multicomponent diffusion of hydrophobic solutes and surfactants in microemulsions. The three solutes pentanol, octanol, and heptane were examined in microemulsions formed from decaethylene glycol monododecyl ether (C12E10) and sodium dodecyl sulfate (SDS). These coefficients are compared with relevant binary and effective binary diffusion coefficients, and also with ternary diffusion coefficients reported in the literature. It is shown that a strong coupling exists between the diffusion of hydrophobic solutes and surfactant in solute-containing microemulsions. In particular, the presence of a gradient in the concentration of the solute can induce a surprisingly large flux of surfactant either up or down the solute gradient. Within the framework of irreversible thermodynamics, these results indicate that hydrophobic solute molecules significantly alter the chemical potential of the surfactant in microemulsions. These effects are present to a comparable degree for both the nonionic C12E10 and ionic SDS microemulsions